The impact of emotional neglect on bystander behavior in cyberbullying: The mediating role of loneliness - Lin, XiaoKang; An, Jie; Zheng, Haoyuan; Tian, Yunlong; Yuan, Xiwen (Edelweiss Applied Science and Technology, 2024)
Bystanders play a crucial role in cyberbullying and are key to intervening in such events. However, previous research has rarely examined the impact of emotional neglect and loneliness on the behavior of bystanders in cyberbullying incidents. Therefore, this study aims to investigate the relationship between emotional neglect and the behavior of cyberbullying bystanders, as well as the mediating role of loneliness in this context. A total of 511 college students were recruited to take part in this study via online survey. The results indicated that emotional neglect was positively associated with loneliness. Loneliness mediates the relationship between emotional neglect and negative cyberbullying bystander behaviors, including promoting the bull and remaining an outsider. This research enhances our understanding of how parental emotional neglect affects bystander behavior in cyberbullying, offering a new perspective for effectively reducing the occurrence of cyberbullying incidents.